Konvergensi Siaran “Dialog Sehat” di Lembaga Penyiaran Publik Lokal (LPPL) Radio Persada FM Blitar - Risma Erina A'ini; Harliantara, Harliantara (Translitera : Jurnal Kajian Komunikasi dan Studi Media, 2023)
The current development of communication and information technology has affected the broadcasting world and has brought about a new phenomenon of convergence. Convergence is not unavoidable by Computer Mediated Communication or CMC. The purpose of this research is to find out of Transmission Convergence Interactive Health Dialogue “Healthy Dialogue” at Local Public Broadcasting Institute (LPPL) Radio Persada FM. The research used qualitative research methods. This research's findings demonstrate that prior to Convergence, Broadcast “Healthy Dialogue” At Local Public Broadcasting Institute Radio Persada FM Blitar only relied on Audio, but it may also be seen, making the message more engaging for audiences and producers. Local Public Broadcasting Institute (LPPL) Radio Persada FM Blitar used 9 characteristics of Computer Mediated Communication (CMC), The theory formulated by Roger (1986: 21) as CMC is more accessible, documented, and existing, it can be used as a method for retaining listeners.